Предмет: Алгебра,
автор: syrymbeisembecov
упростите выражение cosx/(1-sin²x)+cosx/(1+sin²x)
Ответы
Автор ответа:
0
Автор ответа:
0
упростите выражение cosx/(1-sin²x)+cosx/(1+sin²x) =
( cosx/cos²x)+cosx/(1+sin²x)=1/cosx+cosx/(1+sin²x)=(1+cos²Х+sin²x)/cosx/(1+sin²x)=
2/cosx/(1+sin²x)
( cosx/cos²x)+cosx/(1+sin²x)=1/cosx+cosx/(1+sin²x)=(1+cos²Х+sin²x)/cosx/(1+sin²x)=
2/cosx/(1+sin²x)
Похожие вопросы
Предмет: Математика,
автор: tohtaevafiruza08
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: abrakadabra12377
Предмет: Литература,
автор: savinaolga24078
Предмет: Математика,
автор: spakzmt98